Association between modified frailty index and postoperative delirium in patients after cardiac surgery: A cohort study of 2080 older adults - Cheng, Hongtao; Ling, Yitong; Li, Qiugui; Li, Xinya; Tang, Yonglan; Guo, Jiayu; Li, Jing; Wang, Zichen; Ming, Wai‐kit; Lyu, Jun (CNS neuroscience & therapeutics, 2024)
Aim To evaluate the association between frailty and postoperative delirium (POD) in elderly cardiac surgery patients. Methods A retrospective study was conducted of older patients admitted to the intensive care unit after cardiac surgery at a tertiary academic medical center in Boston from 2008 to 2019. Frailty was measured using the Modified Frailty Index (MFI), which categorized patients into frail (MFI ≥3) and non‐frail (MFI = 0–2) groups. Delirium was identified using the confusion assessment method for the intensive care unit and nursing notes. Logistic regression models were used to examine the association between frailty and POD, and odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results Of the 2080 patients included (median age approximately 74 years, 30.9% female), 614 were frail and 1466 were non‐frail. The incidence of delirium was significantly higher in the frail group (29.2% vs. 16.4%, p < 0.05). After adjustment for age, sex, race, marital status, Acute Physiology Score III (APSIII), sequential organ failure assessment (SOFA), albumin, creatinine, hemoglobin, white blood cell count, type of surgery, alcohol use, smoking, cerebrovascular disease, use of benzodiazepines, and mechanical ventilation, multivariate logistic regression indicated a significantly increased risk of delirium in frail patients (adjusted OR: 1.61, 95% CI: 1.23–2.10, p < 0.001, E‐value: 1.85). Conclusions Frailty is an independent risk factor for POD in older patients after cardiac surgery. Further research should focus on frailty assessment and tailored interventions to improve outcomes. This study showed a statistically significant association between higher frailty, as assessed by the MFI, and an increased risk of postoperative delirium in older cardiac surgery patients. In order to improve outcomes in this vulnerable population, the need for personalized intervention strategies was highlighted.